Recent advances on sampling methods and educational statistics in honor of S. Lynne Stokes - Stokes, S. Lynne; Springer; Ng, H. K. Tony; Heitjan,Daniel Francis (2022)
This edited collection commemorates the career of Dr. S. Lynne Stokes by highlighting recent advances in her areas of research interest, emphasizing practical applications and future directions. It serves as a collective effort of leading statistical scientists who work at the cutting edge in statistical sampling. S. Lynne Stokes is Professor of Statistical Science and Director of the Data Science Institute at Southern Methodist University, and Senior Fellow at the National Institute of Statistical Sciences. She has enjoyed a distinguished research career, making fundamental contributions to a variety of fields in statistical sampling. Reflecting on Professor Stokes' main areas of research, this volume is structured into three main parts: I. ranked-set sampling, judgment post-stratified sampling, and capture-recapture methods II. nonsampling errors in statistical sampling III. educational and behavioral statistics This collection will be of interest to researchers, advanced students, and professionals in the public and private sectors who would like to learn more about latest advancements in statistical sampling, particularly those who work in educational and behavioral statistics
1. Predictive modelling and judgement post-stratification
2. Judgment post-stratified sampling: A comparison with ranked-set sampling
3. Efficient sample allocation by local adjustment for unbalanced ranked-set sampling
4. On the versatility of capture-recapture modeling: We cant count what we dont see
5. Advances in the use of capture-recapture methodology in the estimation of U.S. census coverage error
6. Measurement issues in synthesizing survey-item responses
7. Effects of two sources of nonsampling error in fishing surveys
8. Triple system estimation with erroneous enumerations
9. Record linkage in statistical sampling: Past, present, and future
10. A Bayesian latent variable model for analysis of empathic accuracy in psychology
11. Variance Estimation for Random-Groups Linking in Large-Scale Survey Assessments
12. Item Response Theory and Fisher Information for Small Tests
13. Statistical Evaluation of Process Variables: A Case Study on Writing Tool Usage in Educational Survey Assessment.
Includes bibliographic reference and index
Keywords: Educational statistics Methodology -- Sampling (Statistics) Methodology